2009
DOI: 10.1002/qj.374
|View full text |Cite
|
Sign up to set email alerts
|

Sources of water vapour contributing to the Elbe flood in August 2002—A tagging study in a mesoscale model

Abstract: ABSTRACT:In this study we investigate the contribution of various moisture sources to the Elbe flood that occurred in Central Europe during August 2002. An 8-day simulation with the mesoscale numerical weather prediction model CHRM, including newly implemented water vapour tracers, has been performed. According to the simulation, rather than drawing moisture from one single dominant source region, water vapour from widely separated moisture sources contributed to the extreme precipitation in the most affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 53 publications
3
104
0
Order By: Relevance
“…Elbe and Danube catchments (Ulbrich et al, 2003a, b;James et al, 2004;Sodemann et al, 2009), and in 2005 again in the catchments of Danube and the Swiss Rhine tributary Aare (Zängl, 2007a, b;Hohenegger et al, 2008). All these recent floods happened in the summer and their meteorological setting involved extratropical cyclones of type "Vb", which refers to a special category of cyclone tracks in Europe (van Bebber, 1891).…”
Section: M Grams Et Al: Central European Floods In June 2013mentioning
confidence: 99%
See 1 more Smart Citation
“…Elbe and Danube catchments (Ulbrich et al, 2003a, b;James et al, 2004;Sodemann et al, 2009), and in 2005 again in the catchments of Danube and the Swiss Rhine tributary Aare (Zängl, 2007a, b;Hohenegger et al, 2008). All these recent floods happened in the summer and their meteorological setting involved extratropical cyclones of type "Vb", which refers to a special category of cyclone tracks in Europe (van Bebber, 1891).…”
Section: M Grams Et Al: Central European Floods In June 2013mentioning
confidence: 99%
“…Similarly, for an eastern European flood event in May 2010, Winschall et al (2014) found continental moisture sources to be crucial for the heavy precipitation in addition to important moisture sources in the North Atlantic and Mediterranean. Also James et al (2004) stressed the importance of continental moisture sources for the 2002 Elbe flood, although this event was characterised by a variety of moisture sources (Sodemann et al, 2009). …”
Section: Precipitation Cyclone Tracks and Moisture Sourcesmentioning
confidence: 99%
“…In this study we use the limited-area model CHRM with a water vapour tagging technique implemented by Sodemann et al (2009). See also Sodemann et al (2009) for an overview of previous water vapour tagging applications.…”
Section: Water Vapour Taggingmentioning
confidence: 99%
“…For the parametrized subgridscale processes that affect phase changes like stratiform and convective precipitation, all transfer rates of tagged moisture are considered proportional to the fraction of tagged water and the respective total transfer rate. For more technical information on the tagging implementation see Sodemann (2006) and Sodemann et al (2009). The only difference of the tagging implementations used in this study is a corrected bug in the parametrization of the evapotranspiration of tagged water vapour from land surfaces, which leads to an increase of tagged land evapotranspiration compared to the previous version.…”
Section: Water Vapour Taggingmentioning
confidence: 99%
See 1 more Smart Citation